Cyclodextrins for the Delivery of Bioactive Compounds from Natural Sources: Medicinal, Food and Cosmetics Applications - Stamatia Christaki; Eleni Spanidi; Eleni Panagiotidou; Sophia Athanasopoulou; Anastasia Kyriakoudi; Ioannis Mourtzinos; Konstantinos Gardikis (MDPI AG, 2023)
Cyclodextrins have gained significant and established attention as versatile carriers for the delivery of bioactive compounds derived from natural sources in various applications, including medicine, food and cosmetics. Their toroidal structure and hydrophobic cavity render them ideal candidates for encapsulating and solubilizing hydrophobic and poorly soluble compounds. Most medicinal, food and cosmetic ingredients share the challenges of hydrophobicity and degradation that can be effectively addressed by various cyclodextrin types. Though not new or novel-their first applications appeared in the market in the 1970s-their versatility has inspired numerous developments, either on the academic or industrial level. This review article provides an overview of the ever-growing applications of cyclodextrins in the delivery of bioactive compounds from natural sources and their potential application benefits.